Earthworm fauna (Oligochaeta: Lumbricidae) of Croatian Pannonian mountains—Papuk and Požeška gora - Kutuzović, Davorka Hackenberger; Trakić, Tanja; Glavaš, Olga Jovanović; Plavac, Tena; Kutuzović, Branimir Hackenberger (Zootaxa, 2025)
In this paper a list of earthworm species of the Pannonian mountains in Croatia: Papuk and Požeška gora is presented. The Papuk Mountain, a Nature Park, has been sampled before, with 18 earthworm species recorded, while no records exist for Požeška gora. For this study 120 sites were sampled in 2020 and 2021. A total of 11 genera and 21 species were identified for Papuk Mt and nine genera and 13 species for Požeška gora, all of which belong to the Lumbricidae family. With previous findings, the number of earthworm species for Papuk is 23, representing a third of all known species in Croatia. A total number of species for both mountains is 26. An overview of the zoogeographical types and ecological categories of identified species is also given. Out of three endemic species described for Papuk Mt, we sampled only one, Dendrobaena papukiana Mršić, 1988, at five sites. Overall, our results highlight the richness of the earthworm fauna of Papuk and Požeška gora. These data could help in future assessments of the conservation status of the species, both in Croatia and throughout their range.